2020
DOI: 10.3332/ecancer.2020.1057
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the carers: safeguarding oncologists’ mental health in the time of COVID-19

Abstract: Taking care of patients with chronic, terminal diseases presents unique challenges to the mental health of medical oncologists. The current coronavirus disease 2019 (COVID-19) pandemic has exacerbated these mental health risks brought about by isolation and exhaustion. Delegated to be a national COVID-19 referral centre, the University of the Philippines-Philippine General Hospital faced many challenges, including the increased workload in a perilous and anxiety-inducing national crisis which placed the entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Patients have reported reduced access to support systems and treatment options for substance use disorders 90 as well as an inability to do many things that are normally recommended to them (more sleep, less stress, and more exercise). 91 Patients have also lost access to childcare, caregiver support, and many other resources because of the pandemic and subsequent economic downturn. A survey by the American Cancer Society found that both patients in active treatment and in survivorship care are delaying visits.…”
Section: Goals For Cancer Care Deliverymentioning
confidence: 99%
“…Patients have reported reduced access to support systems and treatment options for substance use disorders 90 as well as an inability to do many things that are normally recommended to them (more sleep, less stress, and more exercise). 91 Patients have also lost access to childcare, caregiver support, and many other resources because of the pandemic and subsequent economic downturn. A survey by the American Cancer Society found that both patients in active treatment and in survivorship care are delaying visits.…”
Section: Goals For Cancer Care Deliverymentioning
confidence: 99%
“…94 Individual burnout interventions have been implemented at the organizational level. [95][96][97][98][99][100][101] These train-the-trainer interventions should be strongly encouraged as an ethical response for clinician care. 86 For example, well-accepted, empirically validated, efficacious approaches such as MBSR and cognitive behavioral therapy address unhelpful thoughts and fears to foster self-compassion.…”
Section: Improving Oncologist Well-beingmentioning
confidence: 99%
“…Studies have shown that thyroid cancer was a common diagnosis among patients admitted to the hospital during the COVID-19 outbreak [ 4 , 14 , 18 ], while the number of fine-needle aspiration (FNA) and radioactive iodine treatments greatly reduced [ 19 , 20 ] and the diagnosis and treatment of patients were severely affected. Since the outbreak of COVID-19, there have been several studies of psychological health status in the general population [ 3 , 21 ], as well as in specific populations such as medical students, health care workers, and cancer patients [ 22 27 ], while no studies have been conducted specifically on the psychological status of patients with thyroid cancer during the COVID-19 period, which deserves attention.…”
Section: Introductionmentioning
confidence: 99%